The Legal Protection for Buyer in Deed of Selling By Using A Substitute Certificate - Avia Surya Ningrum; Jawade Hafidz; Widayati Widayati; Peni Rinda Listyawati (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
This study aims to identify and analyze legal protection for land buyers whose certificates use a substitute certificate in the deed of sale and purchase, know and analyse legal certainty of the existence of a replacement certificate if it is charged with mortgage rights and knowing and analyzing examples of sale and purchase deeds using a replacement certificate. The approach method in this research was a normative juridical approach, the research specification was descriptive analytical. The data required includes primary data taken by the literature study method. The data analysis method used descriptive qualitative analysis method. Based on the research concluded that the legal protection for land buyers whose certificates use a replacement certificate in the deed of sale basically the same as legal protection for ordinary Land Rights Certificates. For parcels of land for which a certificate of replacement of land rights has been issued, the Land Office will cancel by law and withdraw and destroy the old certificates that have been previously issued so that one day it does not cause legal disputes. Legal certainty of the existence of a replacement certificate if a mortgage is charged is from: UUPA and Government Regulation Number 24 of 1997 concerning Land Registration in Article 32 paragraph (1) The second certificate (substitute) is a certificate of land rights issued by the Land Office as a substitute for the lost first certificate of the same parcel of land, in this case the subject of the rights the same and the object is also the same. So that the replacement certificate can also be used as collateral for one's debt to financial institutions, both banks and non-banks. The certificate is used as collateral from a financial institution, both bank and non-bank, then the certificate is burdened with mortgage rights, so that because of the legal guarantee of ownership of the land, someone can receive it as securities.